Analysis of the Cellular Mechanism of Antitumor Responses and Autoimmunity in Patients Treated with CTLA-4 Blockade - Maker, Ajay V. (2005)
We have demonstrated previously that the administration of CTLA-4 blockade has mediated objective cancer regression and autoimmunity in patients with metastatic melanoma. To explore the mechanism of these in vivo effects, we have studied the changes in lymphocyte phenotype and function in patients receiving anti-CTLA-4 Ab (MDX-010). Patients with stage IV melanoma or renal cell cancer were treated every 3 wk with an anti-CTLA-4 Ab with or without peptide immunization. Pheresis samples were analyzed using flow cytometry to determine lymphocyte cell surface markers. Gene expression analyses and proliferation assays were conducted on purified T cell subsets. Anti-CTLA-4 Ab did not inhibit the suppressive activity of CD4(+)CD25(+) cells in vitro or in vivo. In addition, there was no decrease in the expression of CD4(+)CD25(+) cells in whole PBMC, nor a decrease in Foxp3 gene expression in the CD4(+) or CD4(+)CD25(+) purified cell populations posttreatment. The percentage of CD4(+), CD8(+), CD4(+)CD25(+), and CD4(+)CD25(−) T cells in PBMC expressing the activation marker HLA-DR increased following anti-CTLA-4 Ab administration. Therefore, our results suggest that the antitumor effects of CTLA-4 blockade are due to increased T cell activation rather than inhibition or depletion of T regulatory cells.